Pengaruh Leverage, Growth Opportunity dan Profitability terhadap Cash Holding serta Firm Value pada Perusahaan LQ45 Periode 2019-2024 (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of leverage, growth opportunity, and profitability on cash holdings and firm value in companies included in the LQ45 index on the Indonesia Stock Exchange during the 2019–2024 period. The research method used is quantitative with a path analysis approach based on panel data. A total of 23 companies were selected as samples using a purposive sampling technique, based on the criteria of companies that are consistently included in the LQ45 index during the study period. The total data analyzed consisted of 138 financial reports. Data processing was carried out using EViews 12 software. The results show that leverage has a negative effect on cash holdings, while profitability has a positive effect on cash holdings. On the other hand, growth opportunity has no significant effect on cash holdings. Furthermore, leverage, growth opportunity, and cash holding have no significant effect on firm value, while only profitability has been shown to have a positive effect on firm value. These findings indicate that profitability is a key indicator in increasing firm value in the Indonesian capital market environment.